2021
DOI: 10.3390/app11030958
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Graph and Safety Potential Field Theory-Based Vehicle Platoon Formation and Optimization Method

Abstract: Platooning is considered to be a very effective method for improving traffic efficiency, traffic safety and fuel economy under the connected and automated environment. The prerequisite for realizing these advantages is how to form a platoon without any collisions and how to maintain and optimize the car-following behavior after platoon formation. However, most of the existing studies focus on the platoon configuration and information transmission method, while only a few attempt to address the issue of platoon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Akopov A.S et al [31] proposed a multi-agent fuzzy transportation system to enhance the maneuverability of both manned and unmanned ground vehicles within the transportation network. Linheng Li et al [32] proposed a novel platoon formation and optimization model combining graph theory and safety potential field theory for connected and automated vehicles (CAVs) under different vehicle distributions. Jicheng Chen et al [33,34] used a vehicular ad hoc network (VANET) for the effective identification and coordination of vehicle platoons, thereby enhancing the safety and performance of platooning systems.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Akopov A.S et al [31] proposed a multi-agent fuzzy transportation system to enhance the maneuverability of both manned and unmanned ground vehicles within the transportation network. Linheng Li et al [32] proposed a novel platoon formation and optimization model combining graph theory and safety potential field theory for connected and automated vehicles (CAVs) under different vehicle distributions. Jicheng Chen et al [33,34] used a vehicular ad hoc network (VANET) for the effective identification and coordination of vehicle platoons, thereby enhancing the safety and performance of platooning systems.…”
Section: Research Backgroundmentioning
confidence: 99%
“…As a kind of virtual force method, the basic idea of artificial potential field is to establish different potential fields to control the movement of the vehicle. Li et al [30] proposed a new formation optimization method. This method was derived from the combination of graph theory and safety potential field theory and was applicable to different vehicle distribution.…”
Section: Related Work/literature Reviewmentioning
confidence: 99%
“…The simulation results demonstrated that this approach accommodates the diverse control requirements of self-driving vehicles across various road traffic conditions. Li et al [19][20][21] developed a CF model grounded in potential driving risk fields, integrating model predictive control with artificial potential fields to formulate a control method for CAV platoons. They further constructed a platoon formation and optimization model by combining the graph theory with the safety potential field theory and validated the efficacy of this control strategy.…”
Section: Introductionmentioning
confidence: 99%